Subversion of Patriarchal Discourse in Meridian - Chapagaee, Rajendra Prasad (Journal of Development Review, 2023)
Walker in her novel Meridian, criticizes patriarchal society’s expectations of woman's roles and advocates about women's individuality and independence. The novel examines its title character Meridian’s emergence as a liberated strong woman. It observes Meridian's attempts to break the patriarchal tradition and how she brings an end to the racism and segregation. It also studies the lives and revolutionary activities of black women who played crucial roles to bring subversion in patriarchal discourse. Initially suspended black woman of patriarchal society, Meridian, the protagonist of the novel, becomes a liberated woman as she knows what she should borrow from the past for the present to create a new future. She breaks most of the generally accepted patriarchal norms and values that govern her society. Though she grows up in the racist, sexist and patriarchal society, she rebels against oppressive systems to attain her self-identity and selfhood. She considers marriage a false institution and deserts it as a challenge to the patriarchal ideology. She challenges the patriarchal image of womanhood and motherhood and presents herself as a liberated woman rather than a submissive wife and loving mother. She disobeys the patriarchal rules made for women and rejects any of the life-narratives of her patriarchal society. She starts her journey in search of meaningful personal and political life. She subverts all sorts of patriarchal discourses dominant in racist and sexist society. She finally paves a path of liberty with self identity and selfhood for herself and for the whole women. The paper tracks Meridian’s experiences from her college life to her self-determining liberated woman of present. She is free to love men without the burdens of marriage, sexual restriction and motherhood. It also explores black women's hidden strength, their beauty and feelings of sisterhood and wifehood. The study reveals how Meridian, revolts against the patriarchal ideologies to regain her lost identity and wholeness.